(untitled) (Scientific journal of the Fergana State University, 2024)
Today it is no secret that medicinal plants play an important role in the prevention and treatment of various diseases in modern and traditional medicine. In the development of this direction, along with representatives of the local flora, introduced plants also make a healthy contribution. In particular, a number of plants have been acclimatized in our country, which are mainly used in landscaping cities and creating eco-parks, in the food, perfume, and pharmaceutical industries. This article presents the healing and beneficial properties of flax and castor beans. phenolic compounds contained in sea buckthorn and nettle plants were studied using high-quality liquid chromatography.